From Silence to Strength: A Women-centered Framework in Faith-based Community Organizing - Hamidah, Kamilia; Hussin, Sabariah; Naharin, Sri (Sawwa: Jurnal Studi Gender, 2024)
Three models of community organizing (CO) are commonly used as paradigms: the conventional Alinsky’s, faith-based community organizing (FBCO), and the women-centered model. However, few studies on CO that focus on integrating these three models as a comprehensive lens of analysis. The women-centered community organizing paradigm lacks religio-spiritual complexity, which hinders the acceptance of women empowerment’s message among religious communities. This study aims to propose a practical community-organizing model by synthesizing three different community-organizing models carried out by religious-based women non-governmental organizations. This study combines a systemic literature review method and a qualitative approach to study women-based CSOs. The finding indicates that integrating three community organizing (CO) models effectively empowers women.